Trace fossils, algae, invertebrate remains and new U-Pb detrital zircon geochronology from the lower Cambrian Torneträsk Formation, northern Sweden. (3rd July 2021) - McLoughlin, Stephen; Vajda, Vivi; Topper, Timothy P.; Crowley, James L.; Liu, Fan; Johansson, Ove; Skovsted, Christian B.
ABSTRACT: Nineteen ichnotaxa, together with algal and invertebrate remains, and various pseudo-traces and sedimentary structures are described from the Torneträsk Formation exposed near Lake Torneträsk, Lapland, Sweden, representing a marked increase in the diversity of biotic traces recorded from this unit. The "lower siltstone" interval of the Torneträsk Formation contains mostly simple pascichnia, fodinichnia and domichnia burrows and trails of low-energy shoreface to intertidal settings. The assemblage has very few forms characteristic of high-energy, soft-sediment, foreshore or upper shoreface environments (representative of the Skolithos ichnofacies). Uranium-lead (U-Pb) LA-ICPMS analysis of zircon from a thin claystone layer within the "lower siltstone" interval yielded a maximum depositional age of 584 ± 13 Ma, mid-Ediacaran. Most of the zircon is represented by rounded detrital grains that yield dates between 3.3 and 1.0 Ga. Although the age of the basal sandstone-dominated interval of the Torneträsk Formation remains elusive owing to the absence of fossils, the ichnofossil suite from the overlying "lower siltstone" interval lacks deep arthropod trackways, such as Rusophycus and Cruziana, and is suggestive of a very early (Terreneuvian, possibly Fortunian) Cambrian age. The ichnofauna is otherwise similar to early Cambrian trace fossil assemblages from other parts of Baltica, regions further south in modern Europe, and from Greenland.